SAT0445 Survival of Tocilizumab Therapy in Children with Systemic Juvenile Idiopathic Arthritis. Russian Experience. (23rd January 2014) - Denisova, R.; Alekseeva, E.; Valieva, S.; Bzarova, T.; Isayeva, K.; Sleptsova, T.; Mitenko, E.; Chistyakova, E.; Fetisova, A.
Abstract : Background: Systemic juvenile idiopathic arthritis (sJIA) is the most severe subtype of JIA; treatment options are limited. Interleukin-6 plays a pathogenic role in systemic JIA. Objectives: To evaluate survival of tocilizumab treatment in sJIA. Methods: An open observational study in patients with sJIA taking tocilizumab. A total of 109 patients (51 boys and 57 girls) were included in this study. Analysis of survival tocilizumab treatment was performed in all patients by Kaplan–Meier curve. Results: Tocilizumab treatment survival at 6 months was 92% (n=86), at 12 months was 85% (n=66), at 18 months was 79% (n=33), at 24 months was 79% (n=18), at 36 months was 71% (n=5). Tocilizumab treatment was discontinued in 19 patients during the follow-up 36 months period. The causes for cancellation were relapse of disease (n=9), lack of efficacy (n=5), remission (n=1), parent's refusal (n=1), infusion reaction (n=2) and Crohn's disease (n=1). Patients with systemic features of flare were switched to canakinumab and rituximab (7 and 3, consequently), patients without systemic features but with arthritis flare were switched to adalimumab (n=4). Image/graph: Conclusions: The high percent of survival was registered after year of tocilizumab treatment in patients with sJIA. In addition there were no serious infection adverse events as the cause of discontinuation. Disclosure of Interest: None Declared